Industrial internet of things : cybermanufacturing systems - Jaschke, Sabina; Brecher, Christian; Song, Houbing; Rawat, Danda B., 1977- (Springer, 2017)
Developing the core system science needed to enable the development of a complex industrial internet of things/manufacturing CPS (IIoT/M-CPS), this book will foster a research community committed to advancing research and education in IIoT/M-CPS and to transitioning applicable science and technology into engineering practice. Presenting the current state IIoT and the concept of cybermanufacturing, this book is at the nexus of research advances from the engineering and computer and information science domains. It features contributions from leading experts in the field with years of experience in advancing manufacturing. Readers will acquire the core system science needed to transform to cybermanufacturing that spans the full spectrum from ideation to physical realization.
Keywords: Cooperating objects (Computer systems); Internet of things.; Robots, Industrial.; elektronické knihy; electronic books